Specificity of Diphtheria Toxin Action on Heart and Muscle Tissues of Guinea Pigs - Bowman, C. G. (1970)
Heart and muscle tissues appear to be specific target organs for the in vivo inhibition of protein synthesis by diphtheria toxin.